Two-Phase Expander Approach for Next Generation of Heat Recovery Systems - Panesar, Angad S; Bernagozzi, Marco (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
This study presents the numerical adaptations to the semi-empirical expander model in order to examine the feasibility of piston expanders under off-design and two-phase scenarios. This expander model considers supply valve pressure drop, condensation phenomena, heat losses, leakage losses and friction losses. Using Aspen HYSYS©, the expander model is utilised in simulating the next generation of integrated engine cooling and exhaust heat recovery system for future heavy-duty engines. The heat recovery system utilises water-propanol working fluid mixture and consists of independent high pressure (HP) and low pressure (LP) expander. The results of off‑design and two-phase operation are presented in terms of expander efficiency and the different sources of loss, under two distinctive engine speed-load conditions. The heat recovery system, operating with the LP expander at two-phase and the HP expander at superheated condition, represented the design point condition. At the design point, the system provided 15.9 kW of net power, with an overall conversion efficiency of 11.4%, representing 10% of additional engine crankshaft power. At the extreme off-design condition, the two-phase expander operation improved the system performance as a result of the nullification of leakage losses due to the much denser working fluid. The optimised two-phase operation of the LP expander (x=0.55) and the HP expander (x=0.9) at the extreme-off design condition improved the system power by nearly 50% (17.4 vs. 11.7 kW) compared to the reference state. Finally, adapting piston air motors as two-phase expanders for experimental evaluation and reduction in frictional losses was a recommended research direction. ©2019. CBIORE-IJRED. All rights reserved